A prospective study comparing the inflammation-related cytokine and chemokine profile from the day of blastocyst transfer to 7 weeks of gestation between pregnancies that did or did not result in a miscarriage. (December 2022) - Zhao, Yiwei; Man, Gene Chi Wai; Zhang, Ruizhe; Wong, Chun-Kwok; Chen, Xiaoyan; Chung, Jacqueline Pui-Wah; Wang, Chi-Chiu; Laird, Susan; Zhang, Tao; Li, Tin-Chiu
Abstract: The dynamics of maternal immunomodulation is essential in early pregnancy. In our previous study, successful implantation is characterized by a transient increase of pro-inflammatory cytokines followed by a switch to an anti-inflammatory state in peripheral blood around 3–6 days after embryo transfer (ET). In this study, we aimed to extend the time points to compare the cytokine and chemokine profiles between women who did or did not subsequently miscarry. We utilized precisely timed serum samples on the day of ET and 3, 6, 9, 16, 23 and 30 days after ET in women undergoing single blastocyst transfer. Our analysis revealed a significant alteration in cytokine profile after day ET+ 9 between the two groups. Regarding pro-inflammatory cytokine profile, there was a significant increase in IL-17 on days ET+ 16, + 23, and + 30 (50.60 ± 9.97 vs 37.09 ± 3.25, 53.20 ± 8.13 vs 36.51 ± 3.34, 57.06 ± 8.83 vs 33.04 ± 3.11 pg/mL), TNF-α on days ET+ 23 and + 30 (73.90 ± 12.42 vs 50.73 ± 3.55, 74.16 ± 12.46 vs 46.59 ± 3.21 pg/mL), IFN-γ on day ET+ 30 (69.52 ± 13.19 vs 42.28 ± 7.76 pg/mL) in women who miscarried compared to women who had a live birth. In contrast, the concentrations of anti-inflammatory cytokines IL-10 on days ET+ 23 and + 30 (26.23 ± 2.11 vs 38.30 ± 4.64, 23.77 ± 2.06 vs 39.16 ± 4.99 pg/mL) and TGF-β1 on day ET+ 30 (20.30 ± 1.25 vs 23.81 ± 0.88 ng/mL) were significantly decreased in women who miscarried compared to women who had a live birth. While for the chemokine profile, there was no significant alteration observed between the two groups across all the time points. These findings suggest that a sustained anti-inflammatory milieu is concomitant with the maintenance of early pregnancy, while the remarkable pro-inflammatory shift as early as day ET+ 16 in women who subsequently miscarried was observed before the diagnosis of miscarriage. Highlights: Maternal immune adaption in response to embryo implantation is dynamic and essential for the maintenance of pregnancy. The levels of peripheral blood inflammation-related cytokines started to show significant differences from day ET+ 16 onwards between pregnancies which did or did not miscarry. In the live birth group, there was a transient and modest increase in serum pro-inflammatory cytokine levels around 3–6 days after ET, which was followed by a sustained increase in anti-inflammatory cytokines from day-9 to day-30 after ET. In the miscarriage group, the transient increase in pro-inflammatory cytokines around 3–6 days after ET was similar to that in the live birth group, while it was followed by a sustained increase in pro-inflammatory cytokines instead of anti-inflammatory cytokines since day ET+ 16.